Comparison of kilometre and sub‐kilometre scale simulations of a foehn wind event over the Larsen C Ice Shelf, Antarctic Peninsula using the Met Office Unified Model (MetUM). (19th August 2021) - Orr, Andrew; Kirchgaessner, Amélie; King, John; Phillips, Tony; Gilbert, Ella; Elvidge, Andrew; Weeks, Mark; Gadian, Alan; Kuipers Munneke, Peter; van den Broeke, Michiel; Webster, Stuart; McGrath, Daniel
Abstract: A foehn event on 27 January 2011 over the Larsen C Ice Shelf (LCIS), Antarctic Peninsula and its interaction with an exisiting ground‐based cold‐air pool is simulated using the MetUM atmospheric model at kilometre and sub‐kilometre scale grid spacing. Atmospheric model simulations at kilometre grid scales are an important tool for understanding the detailed circulation and temperature structure over the LCIS, especially the occurrence of foehn‐induced surface melting, erosion of cold‐air pools, and low‐level wind jets (so‐called foehn jets). But whether there is an improvement/convergence in the model representation of these features at sub‐kilometre grid scales has yet to be established. The foehn event was simulated at grid spacings of 4, 1.5 and 0.5 km, with the results compared to automatic weather station and radiosonde measurements. The features commonly associated with foehn, such as a leeside hydraulic jump and enhanced leeside warming, were comparatively insensitive to resolution in the 4 to 0.5 km range, although the 0.5 km simulation shows a slightly sharper and larger hydraulic jump. By contrast, during the event the simulation of fine‐scale foehn jets above the cold‐air pool showed considerable dependence on grid spacing, although no evidence of convergence at higher resolution. During the foehn event, the MetUM model is characterised by a nocturnal cold bias of around 8 °C and an underestimate of the near‐surface stability of the cold‐air pool, neither of which improved with increased resolution. This finding identifies a key model limitation, at both kilometre and sub‐kilometre scales, to realistically capture the vertical mixing in the boundary layer and its impact on thermodynamics, through either daytime heating from below or the downward penetration of foehn jet winds from above. Detailed model‐resolved foehn jet dynamics thus plays a crucial role in controlling the near‐surface temperature structure over the LCIS, as well as sub‐grid turbulent mixing. Abstract : A foehn wind event on 27 January 2011 over the Larsen C Ice Shelf (LCIS), Antarctic Peninsula and its interaction with an existing cold‐air pool is simulated using the MetUM regional atmospheric model at kilometre and sub‐kilometre scale grid spacing. The features commonly associated with foehn winds, such a leeside hydraulic jump and enhanced leeside warming were comparatively insensitive to resolution in the 4 to 0.5 km range. By contrast, during the event the simulation of fine‐scale foehn jets above the cold‐air pool showed considerable dependence on grid spacing, although no evidence of convergence at higher resolution. During the foehn event the MetUM model is also characterised by a nocturnal cold bias of around 8 °C and an underestimate of the near‐surface stability of the cold‐air pool, neither of which improved with increased resolution. This suggests that the models struggle to realistically capture the vertical mixing in the boundary layer and its impact on thermodynamics, through either daytime heating from below or the downward penetration of foehn jet winds from above.